Áreas prioritárias para restauração no estado de Goiás - Silva, Thalline Rodrigues da (2020)
In parallel with strategies and actions focused on the conservation of biodiversity, scientists, decisionmakers, and different sectors of our society have been developing on strategies focused on the restoration of degraded areas. This is a particularly important issue for Brazil as signatory to the Paris Agreement, in which the Brazilian government is committed to restoring 12 million hectares of degraded areas by 2030. Such restoration will be regionalized, and the states of Brazil will need to indicate their priorities, strategies and tools to accomplish such task. Here, we identified priority areas for restoration in the state of Goiás in order to build scenarios in which the retention of soil carbon stock is maximized, as well as the representation of plant species, while seeking the lowest cost of opportunity to perform this restoration on rural landowners. We ran prioritizations following the principles of systematic conservation planning. We also considered the environmental debt within rural properties and, based on that, we evaluated all types of agricultural culture found on the properties to generate opportunity costs associated with restoration. After analyzing 166,635 rural properties across the state, we found a total debt of approximately 1,682,804.1330 hectares within properties’ Legal Reserve. We also observed that most rural properties that should be restored have an opportunity cost below R$5,000. In all prioritization scenarios, areas to the east and northeast of the state of Goiás were considered as priority. Our best restoration scenario captured ~35% of the state's entire carbon stock, nearly 70% (on average) of the distribution of endangered plant species included in the study and a reduction in opportunity cost of more than 70%. Systematic planning for restoration, as proposed here, if carried out in an organized and accountable way, can maximize the connectivity of protected areas within rural properties, bringing greater protection of species and guarantee of the provision of ecosystem services.